The impact of the corona epidemic on working capital management for jordanian companies listed on the amman stock exchange - Yaser Mohd Hamshari; Mohammad Ahmad Alqam; Haitham Yousef Ali (Cogent Economics & Finance)
The purpose of this study is to examine how the COVID-19 epidemic has affected the working capital management practices of Amman Stock Exchange (ASE) companies. From 2012 to 2021, 101 firms were studied in the financial sector. The data was also examined using a Multiple Regression Model in the study. The results revealed that Covid-19 Pandemic has significant and negative effect on working capital management. According to the results, companies tended to take a relatively conservative approach to managing their working capital. More importantly, the data demonstrated that the COVID-19 pandemic crisis drove changes in working capital management practices. Companies with a high FL, QR, and CCC have attempted to increase their client base by prolonging the average age of their accounts receivable and decreasing the turnover rate of their liabilities, respectively. Companies with a greater CCC, as well as those whose principal current assets are accounts receivable, outperformed the other working capital management strategies.